Peramalan Penjualan Mobil Pada PT Toyota Astra Motor Indonesia Dengan Metode Trend Semi Average Dan Metode Least Square - Isnurrini Hidayat Susilowati (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2022)
The purpose of this study is to determine the car sales volume desired by PT Toyota Astra Motor so that the company can make decisions by conducting sales forecasting. This type of research is carried out in a quantitative descriptive form. Data collection techniques using documentation techniques and carried out by collecting secondary data. The car sales forecasting method at Toyota Astra Motor Indonesia using the semi-average trend method with the 2022 sales forecasting result of 241,301 units and the sales forecasting result in 2022 with the least square method is 244,145 units. The smallest accuracy or error of car sales forecasting is found in the semi-averade trend method with MAD values of 39,685, MSE 2,172,864,066 and MAPE 14.73%.